Enhancing Students’ Communication Skills on Climate Change through Electronic Information of Adaptation and Mitigation - Deden Ibnu Aqil; Ahmad Khoiri; Sisean Baga; Robert Kurniawan (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
Climate change is an ongoing critical issue that has impacted all countries globally, including Indonesia. The major problem in environmental learning is how affected society can adapt and mitigate climate change. The public can quickly obtain information regarding climate change, but educational information on methods to adapt and mitigate climate change still needs to be improved. Students are crucial in assisting the government in educating the public on methods of adapting to and mitigating climate change. In response to rapid technological advancements, Electronic Information of Adaptation and Mitigation (EI-AME) was developed as an interactive digital learning module to support environmental education. This study aims to examine the improvement of students’ communication skills in climate change education through the implementation of EI-AME. The experimental method was used in this research, with a sample of 146 students from two universities in Jakarta, Indonesia. This research's design is a pretest-posttest with a control class. The instrument used consisted of 14 essay questions with 4 different aspects of communication skills. The research outcome revealed that students' communication skills scores significantly increased in the experimental class compared to the control class. This shows that EI-AME can be an innovative teaching material in the future for strengthening students' communication skills. Further research should be conducted to highlight how such communication skills can help students transfer information in society.